The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12884-018-1849-3
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms of disordered eating in pregnancy: a Delphi consensus study

Abstract: BackgroundThis study aimed to establish consensus on the expression and distinction of disordered eating in pregnancy to improve awareness across various health professions and inform the development of a pregnancy-specific assessment instrument.MethodsA three-round modified Delphi method was used with two independent panels. International clinicians and researchers with extensive knowledge on and/or clinical experience with eating disorders formed the first panel and were recruited using structured selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 55 publications
1
19
1
2
Order By: Relevance
“…It is interesting to note that despite reported disorded eating (DE) prevalence between 0.6% and 27.8% among pregnant women in general,36 in our study, neither athletes nor controls (as a group) had average BD or DT scores above cut-off prepregnancy or postpartum. The finding related to the increased DT score for the athletes (and not for the controls) postpartum might be explained by the fact that these athletes were eager to achieve their prepregnancy shape and fitness (ideal body composition) as fast as possible to optimise performance.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…It is interesting to note that despite reported disorded eating (DE) prevalence between 0.6% and 27.8% among pregnant women in general,36 in our study, neither athletes nor controls (as a group) had average BD or DT scores above cut-off prepregnancy or postpartum. The finding related to the increased DT score for the athletes (and not for the controls) postpartum might be explained by the fact that these athletes were eager to achieve their prepregnancy shape and fitness (ideal body composition) as fast as possible to optimise performance.…”
Section: Discussioncontrasting
confidence: 80%
“…It was also an important finding that the number of athletes who met the criteria for ED were lower postpartum compared with prepregnancy and pregnancy. This might indicate that pregnancy per se does not trigger or increase the possibility for maintenance of an ED for elite athletes as indicated in non-athletic women 36…”
Section: Discussionmentioning
confidence: 99%
“…A key issue noted in existing literature (Bannatyne et al, 2018;Easter et al, 2013;Pettersson et al, 2016), and confirmed in this review, is the absence of pregnancy-specific measures of disordered eating. This is in contrast to postnatal depression where several instruments specific to the perinatal period have been developed (e.g., the Edinburgh…”
Section: A Need For Pregnancy-specific Measures Of Disordered Eatingmentioning
confidence: 62%
“…For example, the overlap between pregnancy-related symptomatology and disordered eating pathology could potentially increase the percentage of false positives (i.e., over-identifying pregnancy symptoms as 'disordered') or false negatives (i.e., under-identifying cases of disordered eating by attributing symptoms to pregnancy) on an instrument. Furthermore, recent research (e.g., Bannatyne, Hughes, Stapleton, Watt, & MacKenzie-Shalders, 2018) has indicated the expression of disordered eating in pregnancy may include unique pregnancy-specific features that are not assessed in traditional instruments such as overvaluation of the offspring's weight and shape (e.g., desire for the baby to be "small" or "petite"), rationalisation of self-induced vomiting as pregnancyappropriate, and emotional detachment from the pregnancy.…”
mentioning
confidence: 99%
“…Eating disorders (ED) are mental health disorders characterised by severe disturbances in eating behaviour that significantly impact an individual's emotional, psychosocial and physical well-being (Bannatyne et al 2018). Current diagnostic classifications of ED include anorexia nervosa (AN), bulimia nervosa (BN) and binge-eating disorder (BED) as full threshold ED.…”
Section: Introductionmentioning
confidence: 99%